Active / reactive dispatch in competitive environment - M. H. R. Gomes (2005)
Ancillary Services play an important role in power systems since they are crucial to ensure the security and quality of operation. However, this issue is sometimes forgotten and power systems tend to be analysed only from the point of view of electricity markets to schedule active power. In several countries, active and reactive dispatches were decoupled but in fact this causes several inefficiencies and technical difficulties since their schedules is not independent and the two of them determine the operation conditions of power systems. This paper describes an active / reactive dispatch model that retains the competitive aspects currently in force in power systems. It is based on an initial pool dispatch and on adjustment bids used to change generation or load values namely to accommodate losses or to curtail load if that is required to meet operation or technical constraints. This certainly contributes to clarify the roles of the Market and System Operators and to turn the decisions from the System Operator more robust and justifiable from a technical point of view.